The expectations towards the nurse of the chronically ill patients - Chilińska, Joanna Z.; Krajewska-Kułak, Elżbieta; Kędziora-Kornatowska, Kornelia; Bachórzewska-Gajewska, Hanna (Medycyna Paliatywna/Palliative Medicine, 2016)
Introduction: Satisfaction with nursing care is the most important index of patients’ general satisfaction. Aim of the study : To assess the expectations for nursing staff held by patients with cancer and cardiovascular disorders. Material and methods : Three groups of patients: group I – 120 with early-phase cancer diseases, group II – 150 with terminal-phase cancer diseases, and group III – 160 with cardiovascular disorders, completed a questionnaire involving the Social Support Scale that addressed their expectations of nurses. Results: Patients in group I regarded conscientiousness as the most desired quality of nurses, and 81.3% and 81.9% in groups II and III, respectively, agreed that it was at least important. Also comparably, 77.5% of patients in group I, 74.7% in group II, and 70.6% in group III reported having full trust in nursing staff. Concerning most important skill for nurses to have, patients in group I indicated an ability to pass medical information to patients (89.2%), those in group II indicated accuracy and gentleness in performing medical procedures (62.7%), and those in group III indicated humanitarian attitude toward patients (59.4%). Level of education of nurses did not matter to 50.8% of patients in group I, 54% in group II, and 35% in group III. Conclusions : The expectations of nursing staff concerning professional skills differed significantly depending on type and stage of disease. Patients in all groups esteemed informational and emotional support far more highly than instrumental and evaluating skills.